Interaction effect of cadmium and salicylic acid on proline and enzymatic antioxidant in soybean - Marefat, E.; Shabani, L.; Amooaghaie, R. (Penerbit Universiti Kebangsaan Malaysia, 2012)
Possible mediatory role of salicylic acid in protecting soybean (Glycine max L.) plantlets against cadmium toxicity was investigated. Changes in growth, proline and soluble carbohydrates contents, lipid peroxidation and activities of H2O2 scavenging enzymes in salicylic acid (0.5 mM) treated plantlets of soybean in Hoagland’s solution containing 200 μM CdCl2 were monitored. Results showed that fresh and dry weight of shoots and roots were reduced while proline and soluble carbohydrates contents and lipid peroxidation in leaves of soybean treated with cadmium were significantly increased compared to controls. Guaiacol peroxidase (1.06±0.05, 1.65±0.22), ascorbate peroxidase (42.16±1.09, 57.2±1.68) and catalase (1729.66±20.13, 4345±230.5) activities were significantly enhanced for (-Cd-SA) and (+Cd-SA) treatments respectively. Lipid peroxidation and proline content were lowered by salicylic acid treatment, while soluble carbohydrates were increased. The activities of guaiacol peroxidase, ascorbate peroxidase and catalase were also lesser in leaves of salicylic acid-treated plants. Salicylic acid alleviated cadmium toxicity not only at the level of antioxidant defense, but also by affecting other mechanisms of detoxification.